The INFLUENCE OF YOUTUBE BASED VIDEO TOWARD STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Ihat Nuur Herma Auriana; Ida Nuraida; Fadilla Oktaviana (FKIP, Universitas Banten Jaya, 2021)
The objective of this research was to find out if there is a significant influence of YouTube based video toward students’ achievement in writing recount text. This research is used quasi experimental design. The population of this research was the first students of SMK Daruttaibin Ciwadas Pabuaran. The cluster random sampling was used to take the sample. The sample was two classes, X Pemasaran 1 as the experimental class and X Pemasaran 2 as the control class. The experimental class consisted of 22 students and the control class consisted of 20 students. The instrument of collecting data was pre-test and post-test. From the data analysis, the student’s score of the experimental class in the post test was higher than the students in the pre-test. The mean score of posttest in the experimental class 74.7 was higher than mean score of the control class 67.5. It was found that the result statistic calculation, it was obtained that the value of Tvalue was 1.94 and degree of freedom (df) is 40. In the table of significance 0.05 the value of the significance was 1.68, comparing those values, the result was 1.94>1.68 which means Tvalue score. It means that there is significant influence toward students’ writing skill between the students who were taught using YouTube based video and those who were not. In conclusion, the Ho is rejected and Ha is accepted.